Answer:
y = ac / (a - b - c)
Step-by-step explanation:
y(a - b) = c(y + a)
Distribute
ay - by = cy + ac
Subtract cy from both sides
ay - by - cy = ac
Factor out y
y(a - b - c) = ac
Divide both sides by (a - b - c)
y = ac / (a - b - c)
Answer:
0
Step-by-step explanation:
The + on the zero means the limit as x approaches 0 from the right side
![\lim_{x \to 0^{+} } (\frac{1}{x} - \frac{1}{|x|})\\ \lim_{x \to 0^{+} } (\frac{1}{x} - \frac{1}{x})\\ \lim_{x \to 0^{+} } (0)\\0](https://tex.z-dn.net/?f=%5Clim_%7Bx%20%5Cto%200%5E%7B%2B%7D%20%7D%20%28%5Cfrac%7B1%7D%7Bx%7D%20-%20%5Cfrac%7B1%7D%7B%7Cx%7C%7D%29%5C%5C%20%5Clim_%7Bx%20%5Cto%200%5E%7B%2B%7D%20%7D%20%28%5Cfrac%7B1%7D%7Bx%7D%20-%20%5Cfrac%7B1%7D%7Bx%7D%29%5C%5C%20%5Clim_%7Bx%20%5Cto%200%5E%7B%2B%7D%20%7D%20%280%29%5C%5C0)
I believe it is written as 0.43 <span />
C. So he can find a job that doesn’t include writing
Answer:
4 mph
Step-by-step explanation:
The average speed of an object is given by the total distance covered by the time taken:
![v=\frac{d}{t}](https://tex.z-dn.net/?f=v%3D%5Cfrac%7Bd%7D%7Bt%7D)
where
d is the total distance covered
t is the time taken
in the first part, the person runs for 0.4 hours at a speed of 7 mph, so the distance covered in the 1st part is
![d_1 = v_1 t_1 = (7)(0.4)=2.8 mi](https://tex.z-dn.net/?f=d_1%20%3D%20v_1%20t_1%20%3D%20%287%29%280.4%29%3D2.8%20mi)
Then the distance covered in the second part is
, so the total distance is
(1)
The total time elapsed is 0.4 hours (first part) + 0.8 hours (second part), so
![t=0.4+0.8=1.2 h](https://tex.z-dn.net/?f=t%3D0.4%2B0.8%3D1.2%20h)
So we can write the average speed as
(1)
We want the average speed to be 5 mph,
v = 5 mph
Therefore we can rearrange eq.(1) to find d2:
![d_2 = 1.2v-2.8 = (1.2)(5)-2.8=3.2 mi](https://tex.z-dn.net/?f=d_2%20%3D%201.2v-2.8%20%3D%20%281.2%29%285%29-2.8%3D3.2%20mi)
And therefore, the speed in the second part must be
![v_2=\frac{d_2}{t_2}=\frac{3.2}{0.8}=4 mph](https://tex.z-dn.net/?f=v_2%3D%5Cfrac%7Bd_2%7D%7Bt_2%7D%3D%5Cfrac%7B3.2%7D%7B0.8%7D%3D4%20mph)